La crítica poscolonial y la cuestión del ser: acotaciones preliminares (2012)
This paper aims to elucidate the sense of the category from postcolonial studies has been recognized as colonialidad del ser, which refers to those effects produced by the colonial scourge in the experience of the colonized subject. Beyond explaining colonialist or anti-colonialist, what is sought is to decentralize the discussion and raise it in ontological terms, and from there to recognize the arguments supporting a “naturally supposed ontological difference” laying on a lower level than those who are subject colonization and, therefore, of domination and denial.